ANALISIS LIKUIDITAS PADA PERUSAHAAN FOOD AND BEVERAGE - Endang Purwanti (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
This study aims to determine the Financial Performance of the Liquidity Level of Food and Beverage Companies as measured by the Current Ratio, Quick Ratio, and Cash Ratio. The results showed the liquidity level of seven companies used in the study. In the Current Ratio, six companies had a liquidity level above 100%, so the companies had the ability to meet their short-term obligations. While in the Quick Ratio, there are five companies that have a liquidity level above 100%, then the companies have the ability to meet short-term obligations outside of inventory and have no difficulty in fulfilling short-term obligations. In the Cash Ratio, the companies have a liquidity level below 100%, thus the company does not have the ability to pay short-term obligations from the available cash, and the companies have cash difficulties paying the short-term debt. Companies need to increase the level of liquidity from the ratio quickly, by managing the amount of inventory efficiently and handling the amount of inventory according to needs.